Tatbiq Manhaj TPACK fi Ta'lim al-Lughah al-'Arabiyyah bil Madrasah al-'Aliyah al-Islamiyyah - Mukti, Rahayu; Muhammad Zaenuri; Imam Makruf; Hafidah (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2025)
Technological advances in the digital era demand better integration between technology, pedagogy, and content in learning, especially to increase motivation to learn Arabic which is often considered monotonous. This study aims to describe the implementation of Technological Pedagogical Content Knowledge (TPACK) approach in Arabic learning at MAN 1 Klaten and identify the obstacles faced by teachers. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results showed that the TPACK approach has been well implemented in Arabic language learning. However, there are obstacles in the form of limited access to technology and the need to present material with harakat to make it easier for students to understand. In Arabic language learning, the TPACK approach has a positive impact on student engagement and learning relevance. With further development and improved technological infrastructure, this approach can be optimized to encourage educational innovation and higher learning motivation. This research reinforces the important role of technology in developing engaging and interactive Arabic language learning.